Investigating the Disposition Effect among Young Investors: An Integrative Literature Review on Cognitive Biases - Wahyu Fahrul Ridho; Yanda Bara Kusuma (Jurnal Aplikasi Manajemen dan Bisnis, 2023)
This literature review elucidates the disposition effect, a pervasive behavioral bias causing investors to prematurely sell appreciating assets while retaining depreciating ones, within the context of young investors. In the evolving financial landscape, characterized by an increasing influx of young, often less experienced market participants, understanding the cognitive biases influencing their investment decisions is imperative. This study examines influencing factors and growing body of research regarding cognitive bias in investing among young investors especially disposition effect. It has been found from various literature that disposition effect is prevalent among young and novice investors compared to their counterpart. Despite numerous studies on this topic, research gaps remain regarding the disposition effect among young investors in emerging markets and across different asset classes. Future research should aim to bridge these gaps to foster a generation of competent and informed young investors. This review highlights the need for effective financial education programs tailored to the unique traits and behaviors of young investors, aiding in better investment decision-making and contributing to the health and stability of financial markets.